Valuation of Social Capital in Public Transportation and Sustainable Mobility in Venezuela. A Systematic Review of the Literature - Padron, Carmen Janeth (Revista de Estudios Andaluces, 2021)
In this article, a systematic review was carried out between 2008 and 2020 to identify the valuation of social capital in public transport and sustainable mobility in Venezuela. Within the methodology, the open database Ebscohost was searched, finding 67 studies and when delimiting it according to the inclusion and exclusion criteria, only 5 were related to the subject. Social capital promotes: economic development, overcoming poverty and democratic governance of the countries. Finally, in Venezuela, social capital tends to be negative and precarious, given its economic, social and political crisis, as regards public transport its value is substantial and weak, as there is a lack of integration with other modes of transport and little mobility sustainable.